FRAGMENTATION OF AUTHORITY OF THE FREE NUTRITIONAL MEAL PROGRAM FROM THE PERSPECTIVE OF PUBLIC ADMINISTRATION - Amas Mashudin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The Free Nutritious Meals (MBG) Program is a strategic government policy designed to improve the nutritional status of the community, enhance the quality of human resources, and support efforts to accelerate the reduction of stunting in Indonesia. Despite the high expectations for the program, its implementation still faces various governance issues, particularly those related to the division of authority between government institutions. The involvement of many actors in the planning, budgeting, implementation, and monitoring processes has not been fully accompanied by an effective coordination mechanism, potentially leading to overlapping tasks, differing policy interpretations, and inconsistencies in implementation across regions. Based on these conditions, this study aims to analyze the forms of fragmentation of authority in the implementation of the Free Nutritious Meals Program and explain its implications for the effectiveness of governance from a public administration perspective. The study used a qualitative approach with a case study design. Data were obtained through in-depth interviews with stakeholders, observations of program implementation, and reviews of various policy documents, regulations, and institutional reports related to the MBG implementation. Data were analyzed through thematic analysis using source and method triangulation to strengthen the validity of the research results. The research findings indicate that fragmentation of authority not only impacts the effectiveness of inter-institutional coordination but also results in slow decision-making, administrative inefficiencies, and variations in program implementation at the regional level. Furthermore, the study found that strengthening collaborative governance, clarifying role allocations, harmonizing regulations, and utilizing integrated information systems can improve coordination and enhance the effectiveness of program implementation. Therefore, strengthening institutional synergy and realigning the distribution of authority are crucial prerequisites for realizing a more effective, accountable, and sustainable Free Nutritional Meal Program within the framework of public administration in Indonesia.